2023
DOI: 10.3201/eid2901.221293
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning Surveillance for SARS-CoV-2 Omicron Variants, United Kingdom, November 2021–September 2022

Abstract: the SARS-CoV-2 Immunity and Reinfection Evaluation (SIREN) Study has detected and investigated SARS-CoV-2 reinfections in the United Kingdom; after vaccine rollout, SIREN was adapted to monitor vaccine effectiveness (1-5). As the United Kingdom, like other countries, adapts to the postacute phase of the pandemic and reduced testing availability (6,7), SIREN has an ongoing function in national surveillance. SIREN informs the UK pandemic response by real-time monitoring of emerging variants and determining natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…7 This continued in this current analysis, however the impact was markedly reduced in the Omicron period, and showed evidence of waning just nine months after infection. Given the distinct SARS-CoV-2 variant waves experienced by our cohort, 23 participants in the Omicron analysis who had been infected less than nine months previously were most likely infected by Delta-variant, those infected 9-12 months ago had Alpha-variant infections, and those infected over 15 months ago had Wild-type infections. Possible explanations for this lower protection afforded by a primary infection sustained over 9 months ago could be greater antigenic distance between successive variants, with a less effective neutralisation response to Omicron from a wildtype infection than a Delta infection, or antibody waning over time.…”
Section: Discussionmentioning
confidence: 99%
“…7 This continued in this current analysis, however the impact was markedly reduced in the Omicron period, and showed evidence of waning just nine months after infection. Given the distinct SARS-CoV-2 variant waves experienced by our cohort, 23 participants in the Omicron analysis who had been infected less than nine months previously were most likely infected by Delta-variant, those infected 9-12 months ago had Alpha-variant infections, and those infected over 15 months ago had Wild-type infections. Possible explanations for this lower protection afforded by a primary infection sustained over 9 months ago could be greater antigenic distance between successive variants, with a less effective neutralisation response to Omicron from a wildtype infection than a Delta infection, or antibody waning over time.…”
Section: Discussionmentioning
confidence: 99%
“…Better designed representative sampling would be immensely empowering and is likely possible through well-designed and suitably powered sampling frames. Ideally, this would be addressed through pandemic preparedness planning, enabling sequencing to be focussed at selected sentinel sites globally cognisant of national jurisdictions and the benefit of longitudinal data, as exemplified by a cohort design in the UK [25].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, this would be addressed through pandemic preparedness planning, enabling sequencing to be focussed at selected sentinel sites globally cognisant of national jurisdictions and the benefit of longitudinal data, as exemplified by a cohort design in the UK. [25]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK has also established an early warning tool, trying to extend the monitoring of medical staff to the society ( 43 ). In view of past successful experiences, some researchers suggested that hospitals formulate phased measures to ensure normal operation of public medical care ( 44 ). This type of alert system can provide dynamic practical guidance to respond to the evolving COVID-19 situation ( 45 ).…”
Section: Literature Reviewmentioning
confidence: 99%